Dale Maharidge and Michael Williamson’s ‘Homeland’: de-constructing the rhetoric of consensus in the aftermath of September 11th attacks (Altre Modernità, 2011)
Focusing on Dale Maharidge and Michael Williamson’s reportage Homeland (2004), this essay explores the de-construction of the discursive and cultural strategies of the “state of exception” used to depict 9/11 events and the dialectics between domestic and international politics and economies. The analysis focuses in particular on four elements: the concept of “Ground Zero” and “Homeland” and their use as lexical and symbolic catalysts of nationalism; the forms and the erasure of dissent; the commodification of 9/11 and the Iraqi war; and the relation between the national rhetoric and the transnational economy in the last two decades.
Keywords: 9/11; Homeland; Dale Maharidge; Michael Williamson